Variability of stimulant levels in nine sports supplements over a 9-month period - Attipoe, S.; Cohen, P. A.; Eichner, A.; Deuster, P. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Many studies have found that some dietary supplement product labels do not accurately reflect the actual ingredients. However, studies have not been performed to determine if ingredients in the same dietary supplement product vary over time. The objective of this study was to assess the consistency of stimulant ingredients in popular sports supplements sold in the United States over a 9-month period. Three samples of nine popular sports supplements were purchased over the 9-month period. The 27 samples were analyzed for caffeine and several other stimulants (including adulterants). The identity and quantity of stimulants were compared with stimulants listed on the label and stimulants found at earlier time points to determine the variability in individual products over the 9-month period. The primary outcome measure was the variability of stimulant amounts in the products examined. Many supplements did not contain the same number and quantity of stimulants at all time points over the 9-month period. Caffeine content varied widely in five of the six caffeinated supplements compared with the initial measurement (-7% to +266%). In addition, the stimulants—synephrine, octopamine, cathine, ephedrine, pseudoephedrine, strychnine, and methylephedrine—occurred in variable amounts in eight of the nine products. The significance of these findings is uncertain: the sample size was insufficient to support statistical analysis. In our sample of nine popular sports supplements, the presence and quantity of stimulants varied over a 9-month period. However, future studies are warranted to determine if the variability found is significant and generalizable to other supplements.